Gender distribution and leadership trends in trauma surgery societies. Issue 1 (2nd April 2020) - Foster, Shannon Marie; Knight, Jennifer; Velopulos, Catherine Garrison; Bonne, Stephanie; Joseph, D'Andrea; Santry, Heena; Coleman, Jamie Jones; Callcut, Rachael A
Abstract : Introduction: Women are under-represented in the surgical disciplines and gender bias is believed to play a factor. We aimed to understand the gender distribution of membership, leadership opportunities, and scientific contributions to annual trauma professional meetings as a case study of gender issues in trauma surgery. Methods: Retrospective collection of membership, leadership, presentation and publication data from 2016 to 2018 Trauma/Acute Care Surgery/Surgical Critical Care (TACSCC) Annual Meetings. Gender was assigned based on self-identification in demographic information, established relationships, or public sources. Results: Women remain under-represented with only 28.1% of those ascertaining American Board of Surgery certification in critical care self-identifying as female. The proportion of female members in Eastern Association for the Surgery of Trauma (EAST) was comparable (29.4%), slightly lower for Western Trauma Association (WTA) (19.0%), and lowest for American Association for the Surgery of Trauma (AAST) (12.8%, p<0.05). In contrast, AAST had the highest proportion of female participants in executive leadership (AAST 32.5%, WTA 19.0%, EAST 18.8%) and WTA the highest for committee chairs (WTA 33.3%, AAST 27.8%, EAST 20.5%). AAST had the most significant increase in executive leadership during the last 3 years (AAST 28.6% to 41.6%). Invited lectureships, masters, panelists and senior author scientific contributions demonstrated the largest gap of academic representation of female TACSCC surgeons. Conclusion: Fewer women than men pursue careers in the trauma field. Continuing to provide mentorship, leadership, and scientific recognition will increase gender diversity in TACSCC. We must continue to promote, sponsor, recognize, invite, and elect 'her'. Level of evidence: III, Epidemiology.